Influence of phospholipid types and animal models on the accelerated blood clearance phenomenon of PEGylated liposomes upon repeated injection. (August 2015) - Xu, Huan; Ye, Feifei; Hu, Meina; Yin, Pengpeng; Zhang, Wei; Li, Yan; Yu, Xiu; Deng, Yihui
Abstract When polyethylene glycol (PEG)ylated liposomes were repeatedly injected into the same animal, the second dose of liposomes would rapidly clear from the bloodstream and enhance accumulation in the liver and spleen, and this phenomenon is called "accelerated blood clearance (ABC)". There are many factors known to influence ABC phenomenon, in this study, we mainly focused on the effects of different phospholipids (PL) types and animal models. The effects of PL types on ABC phenomenon were examined by repeating injection of PEGylated liposomes prepared by five different types of PL (hydrogenated soy phosphatidylcholine, egg sphingomyelin, soybean phosphatidycholin, 1, 2-dipalmitoyl-sn-glycero-3-phosphocholine and egg phosphatidycholin) in rats. Dramatically, repeated injection of different types of PL could induce ABC phenomenon altogether. Both t1/2 and AUC of experimental group (EG) were lower significantly than those of control group (CG). Our results also showed that the liver accumulation of second dose increased significantly (p < 0.01) in all EG as compared that of CG. Interestingly, ABC phenomenon of liposomes prepared by unsaturated PL was more obvious than that of saturated PL. All the first dose could induce the antibody (anti-PEG IgM) level increasing significantly (p < 0.01). For different animal models, we found that after repeated injection of PEGylated liposomes, rats, mice, rabbits and guinea pigs could produce ABC phenomenon. Various PL types and animal models could all produce the ABC phenomenon. However, their extent of accelerated clearance differed. ABC phenomenon is possibly a ubiquitous immune phenomenon in life.